Constraints of philanthropy on determining the distribution of biodiversity conservation funding. Issue 1 (13th October 2015) - Larson, Eric R.; Howell, Stephen; Kareiva, Peter; Armsworth, Paul R.
Abstract: Caught between ongoing habitat destruction and funding shortfalls, conservation organizations are using systematic planning approaches to identify places that offer the highest biodiversity return per dollar invested. However, available tools do not account for the landscape of funding for conservation or quantify the constraints this landscape imposes on conservation outcomes. Using state‐level data on philanthropic giving to and investments in land conservation by a large nonprofit organization, we applied linear regression to evaluate whether the spatial distribution of conservation philanthropy better explained expenditures on conservation than maps of biodiversity priorities, which were derived from a planning process internal to the organization and return on investment (ROI) analyses based on data on species richness, land costs, and existing protected areas. Philanthropic fund raising accounted for considerably more spatial variation in conservation spending (r 2 = 0.64) than either of the 2 systematic conservation planning approaches (r 2 = 0.08–0.21). We used results of one of the ROI analyses to evaluate whether increases in flexibility to reallocate funding across space provides conservation gains. Small but plausible "tax" increments of 1–10% on states redistributed to the optimal funding allocation from the ROI analysis could result in gains in endemic species protected of 8.5–80.2%. When such increases in spatial flexibility are not possible, conservation organizations should seek to cultivate increased support for conservation in priority locations. We used lagged correlations of giving to and spending by the organization to evaluate whether investments in habitat protection stimulate future giving to conservation. The most common outcome at the state level was that conservation spending quarters correlated significantly and positively with lagged fund raising quarters. In effect, periods of high fund raising for biodiversity followed (rather than preceded) periods of high expenditure on land conservation projects, identifying one mechanism conservation organizations could explore to seed greater activity in priority locations. Our results demonstrate how limitations on the ability of conservation organizations to reallocate their funding across space can impede organizational effectiveness and elucidate ways conservation planning tools could be more useful if they quantified and incorporated these constraints .